Impact of delayed device re‐implantation on outcomes of patients with cardiovascular implantable electronic device related infective endocarditis. Issue 8 (24th July 2021) - Arshad, Verda; Baddour, Larry M.; Lahr, Brian D.; Khalil, Sarwat; Tariq, Wajeeha; Talha, Khawaja Muhammad; Cha, Yong‐Mei; DeSimone, Daniel C.; Sohail, M. Rizwan
Abstract: Background: Optimal timing of cardiovascular implantable electronic device (CIED) re‐implantation following device removal due to infection is undefined. Multinational guidelines reflect this and include no specific recommendation for this timing, while others have recommended waiting at least 14 days in cases of CIED related infective endocarditis (CIED‐IE). The current work seeks to clarify this issue. Methods: We retrospectively reviewed institutional data at Mayo Clinic, Minnesota of patients aged ≥ 18 years who developed CIED‐IE from January 1, 1991 to February 1, 2016. CIED‐IE was defined as echocardiogram reported device lead or valvular vegetation. Regression analyses were used to relate the risk of clinical outcomes to the interval between CIED removal and re‐implantation and the location of vegetations. Results: A total of 109 patients met study inclusion criteria. A majority (68.8%) of patients were men and the median age was 68.0 years. Transoesophageal echocardiogram (TEE) was performed in 95.4% of patients, with valve vegetations detected in 33.9% (n = 37). Survival analysis comparing patients in whom device re‐implantation was < 14 days vs. ≥14 days, and further categorized by those with and without valve vegetation, showed a significant difference ( P  = 0.028); patients with valve vegetation and reimplantation interval < 14 days had the lowest (58.7%) 12‐month survival. When adjusted for valve vegetation, longer time interval for reimplantation trended toward increased hospital length of stay ( P  = 0.079). Conclusion: Our findings suggest that the recommended 14‐day delay between CIED extraction and re‐implantation in CIED‐IE patients is associated with a survival benefit, but longer length of hospital stay following re‐implantation.